Temperature dependence of volatile organic compound emissions from surface coatings: Inter-species difference observed in real indoor environments and mechanistic understanding - Qiu, Jia; Xie, Di; Li, Yatai; Qu, Yuekun; Ying Liu; Zhu, Tong; Xiong, Jianyin; Liu, YingJun (Building and Environment, 2023)
Coatings often cover two-thirds of the surfaces in indoor environments and represent important sources of indoor volatile organic compounds (VOCs). Temperature is known to affect VOC emission rates from coatings, yet inter-species difference in the temperature dependence still needs to be understood. Based on time-resolved VOC measurements in an indoor air campaign conducted in residences in Beijing, China, we identified dibasic ester (DBE), a solvent mixture often used in coatings, and found that the concentration ratios of DBE components exhibited strong temperature dependence in an apartment when the indoor temperature declined stepwise over a multiweek period. To interpret the observational results, we developed a simplified mechanistic model relating the temperature dependence of VOC emission rates from coated surfaces to the temperature dependence of the diffusion coefficient of the emitted VOCs in the coating layer and further to a predicable molecular property of the emitted VOCs, molar volumes at 0 K, based on the free-volume theory. This correlation was quantitatively verified using the DBE data as well as using the data of alkanes, another set of VOCs that might be emitted from coatings, observed in two apartments in the same campaign. Given that indoor temperature varies considerably over seasons and across regions, the correlation proposed herein may help better predict indoor VOC emissions from coatings.
Keywords: Coating; diffusion; Free-volume theory; Indoor materials; Molecular properties; temperature